2006
DOI: 10.1097/01.blo.0000223995.79894.5e
|View full text |Cite
|
Sign up to set email alerts
|

Safe Zone for the Descending Genicular Artery in the Midvastus Approach to the Knee

Abstract: Minimally invasive total knee arthroplasty is performed using a modified version of the standard total knee arthroplasty without complete knee exposure. Traditional medial parapatellar arthrotomy has been criticized because it may disturb patellar blood flow and the extensor mechanism. Devascularization of the patella leading to osteonecrosis places the patella at risk for fracture. Alternative vastus-orientated approaches have the potential to preserve the descending genicular artery. Although this arterial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…Basarir et al [16] found a 208-408 entry angle of the DGA to the superomedial pole of the patella in defining a safety zone for the midvastus approach for total knee arthroplasty. Visser et al [17] reported similar angles of the DGA, which was easily recognisable during the limited subvastus approach for the distal femur closing wedge osteotomy in their cadaveric study.…”
Section: Discussionmentioning
confidence: 99%
“…Basarir et al [16] found a 208-408 entry angle of the DGA to the superomedial pole of the patella in defining a safety zone for the midvastus approach for total knee arthroplasty. Visser et al [17] reported similar angles of the DGA, which was easily recognisable during the limited subvastus approach for the distal femur closing wedge osteotomy in their cadaveric study.…”
Section: Discussionmentioning
confidence: 99%
“…3,10,11 Midvastus approaches to the knee joint gained popularity because the descending genicular artery is preserved. 23 Limited soft tissue dissection in less invasive knee arthroplasty also avoids splitting of the rectus and limits disruption of patellar blood supply. But, also after standard medial parapatellar arthrotomy, we have found no significant decrease of patellar blood supply.…”
Section: Discussionmentioning
confidence: 99%
“…Medial parapatellar arthrotomy is the most popular approach technique for TKA and is known to be safe. However, an interruption to the blood supply from the medial circumflex arterial network may occur with the medial parapatellar arthrotomy approach 4 . Nicholls et al 5 reported a patellar blood flow reduction of 53% after a medial parapatellar arthrotomy.…”
Section: Discussionmentioning
confidence: 99%